Non-destructive techniques in concrete elements for bridges’ evalutation - Cruz, Ricardo Alfredo; Quintero-Ortiz, Luz Amparo; Galán-Pinilla, Carlos Andrés; Espinosa-García, Elkin Javier (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this work the Non-Destructive Techniques of Ultrasonic Pulse Velocity (UPV), Infrared Thermography and Rebound Hammer, used in concrete bridge elements to determine their applicability in situ, were evaluated. The study was conducted in two phases: the design and development of a concrete bridge representative elements, and their non-destructive testing application.The UPV technique showed a great capacity to assess the concrete matrix uniformity and quality, with low sensitivity to identify the reinforcements’damages. The infrared thermography allowed to identify delaminations located at depths up to 50% of the evaluated slab thickness. With the rebound hammer results, the concrete slabs compressive strength was estimated, but their readings were affected by the coarse aggregate presence.